2018
DOI: 10.2147/opth.s171822
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ocular morbidity among children aged 17 years or younger in the eastern India

Abstract: PurposeChildhood ocular morbidity involves a spectrum of eye diseases that critically impact the mental development, future education and quality of life. However, there is limited evidence about the early detection and appropriate treatment of ocular morbidity in children <20 years. This study was aimed to assess the prevalence and make a comparison between the different types of ocular morbidity in children of both sexes in the age group of 6–17 years in the eastern India.MethodsA cross-sectional survey of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…5,8 However in the study done at Tanzania, the prevalence of squint was found to be only 0.5%. 18 Convergence Insufficiency accounted for 2.44% of cases in our study which is somewhat consistent with the study done by Shrestha et al (3.4%) 16 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…5,8 However in the study done at Tanzania, the prevalence of squint was found to be only 0.5%. 18 Convergence Insufficiency accounted for 2.44% of cases in our study which is somewhat consistent with the study done by Shrestha et al (3.4%) 16 .…”
Section: Discussionsupporting
confidence: 93%
“…Conjunctival disorders comprised 6.01% cases in our study with allergic conjunctivitis being more common than infective conjunctivitis. Reported prevalence of conjunctivitis in urban setting of Nepal is 4.3 % which is somewhat consistent with our results 16 . Geographical location, seasonal variation and personal hygiene are the factors responsible for conjunctival diseases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients examined were from all age group with the maximum numbers in the age group 1 -10 years (18%), subsequently followed by 11 -20 years (16%), 41 -50 years (15.6%) ( Figure 3). These findings are similar to a study done in India and Nigeria that showed that children are affected with ocular morbidity conditions than the older age [12] [13].…”
Section: Discussionsupporting
confidence: 91%
“…[2] Visual impairment in children also affects the parents or caregivers as the service needs of children with VI are high especially the concerns for their education and career support and these challenges are expressed as family stress. [3,4] Majority of the causes leading to VI in children are preventable or treatable and that is why many recent studies have highlighted the importance of preschool vision screening [5][6][7][8] or screening in school children [9][10][11][12] for early detection and prompt management of the problems related to abnormal vision in children. The prevalence of VI in children varies with geographical locations in the world and within countries, facility of eye care services and economic development of the country.…”
Section: Introductionmentioning
confidence: 99%